Land-use planning permission application under Town and Country Planning Act 1976: legal issues and challenges in its implementation / Nur Fitriah Nordin … [et al.] - Nordin, Nur Fitriah; Zukri, Nik Nurliyana Ayunni; Mohd Apandi, Intan Nur Ashilla; Ab-lah, Sitizulaikha (2013)
A statutory provision is a clause in a statute providing for a particular manner. The statutory definition of town and country planning emphasizes that is concerned with planning and controlling use and another development of land. The statutory provision in the context of development plan and planning control cover a wide scope of the provisions under the town and country planning legislation. However, the provision can be seen as vague and inadequate since there are some issues arise in the matter of the development control specifically on the planning application permission process. This led to the less quality of the development being produced. Thus, the purpose of conducting this research is to undertake a comparative study in term of the provisions of laws relating to the development control specifically the application permission process. Apart from that, this study is for the purpose to investigate relevant provisions under the TCPA 1976 governing the planning control in the land-use development, to analyse the issues and challenges in implementing the planning control system and lastly to compare the planning control system in Peninsular Malaysia specifically in Penang with the planning control in United Kingdom and Australia. This study conducted divided into five main stages of preliminary studies, literature review, legal framework, finding and recommendations. Data collection process consist two (2) type of data, namely primary and secondary data. The primary data involved interview with the selected planning authorities involved in planning control. The informant for this research comprises the town and country planning officer from local authorities. The reason for choosing Penang is because Penang is one of the states that still develop and use Town and Country Planning Act 1976 as the main source. The method analysis for this research is the comparative analysis. The reason for using comparative analysis because it is the most suitable type of analysis since it compare with the other country system. The recommendation in this research basically made for the betterment in provision of planning law in Peninsular Malaysia toward betterment of planning law.